Factors Influencing Consumers’ Preference for Purchasing Footwear Brands - Aamir Abbas; Saqib Qamar; Muhammad Shahzad (UW Journal of Management Sciences, 2022)
Objective: Objective of the present study was to analyze the key factors influencing consumers’ preference and selection for purchasing footwear brands. Methodology: In order to assess the factors influencing consumers’ footwear brands preference, Students of three departments i.e. Institute of Health Management; Dow College of Pharmacy and Institute of Medical Technology of Dow University of Health Sciences were selected for the data collection. A sample size of 150 respondents was recruited by using convenience sampling technique. Data was analyzed with the help of Statistical Package of Social sciences (SPSS 22). Correlation, Anova and Regression analysis was applied to analyze the relationship of independent variables and the dependent variable. Results: Results of correlation, anova and regression analysis shows that there is a significant relationship between price, product quality and consumers’ preference. Recommendation: Present study is beneficial for the footwear manufacturing industry. They have to incorporate product quality in their product since this variable is more influential on the consumers’’ preference. Particularly, they have to build the name of the brand which is recalled in their consumers’ subconscious mind, in terms of features and perceived quality which fulfill their functional benefits.